The use of drawing as communication in aphasias - Cardoso, Maria Cristina de Almeida Freitas (2012)
Aphasia is a language disorder caused by neurological diseases. It affects language in written and oral aspects. This paper aims to analyze drawings used by aphasics as written communication. Eight aphasic participants were asked to write four words and one sentence derived from a picture shown. The results were the following: three participants did not show any disturbance in production and were able to understand the oral request; two participants did drawings only; two others produced both drawings and written answers; one of them only wrote, without drawing. The data brought by the study consolidate the idea of a (re)signification of the language used by this population.